Peutz–Jeghers syndrome: a systematic review and recommendations for management. Issue 7 (25th June 2010) - Beggs, A D; Latchford, A R; Vasen, H F A; Moslein, G; Alonso, A; Aretz, S; Bertario, L; Blanco, I; Bülow, S; Burn, J; Capella, G; Colas, C; et al.
Abstract : Peutz–Jeghers syndrome (PJS, MIM175200) is an autosomal dominant condition defined by the development of characteristic polyps throughout the gastrointestinal tract and mucocutaneous pigmentation. The majority of patients that meet the clinical diagnostic criteria have a causative mutation in the S TK11 gene, which is located at 19p13.3. The cancer risks in this condition are substantial, particularly for breast and gastrointestinal cancer, although ascertainment and publication bias may have led to overestimates in some publications. Current surveillance protocols are controversial and not evidence-based, due to the relative rarity of the condition. Initially, endoscopies are more likely to be done to detect polyps that may be a risk for future intussusception or obstruction rather than cancers, but surveillance for the various cancers for which these patients are susceptible is an important part of their later management. This review assesses the current literature on the clinical features and management of the condition, genotype–phenotype studies, and suggested guidelines for surveillance and management of individuals with PJS. The proposed guidelines contained in this article have been produced as a consensus statement on behalf of a group of European experts who met in Mallorca in 2007 and who have produced guidelines on the clinical management of Lynch syndrome and familial adenomatous polyposis.